ELABORACIÓN DE UN CHORIZO PICANTE A PARTIR DE HARINA DE HABA (Vicia faba) CON ADICIÓN DE GRASA DE CERDO (TOCINO) - Maldonado Velasco, Eduardo Alejandro (2023)
The research project focused on the development of a spicy sausage using fava bean flour (Vicia faba) and pork fat as the main ingredients. The main objective of the thesis was to develop a sausage alternative that is healthy and affordable for consumers, without sacrificing its characteristic flavor and texture. In the course of the research, the product was developed using an experimental design (AxBxC), where Factor A consisted of three temperatures in the chopper (a0=12°C; a1=14°C; a2=16°C), Factor B consisted of two chopper times (b0=17min; b1=20min), and Factor C consisted of two percentages of fava bean flour (c0=22%; c1=24%). The result was the production of 24 experimental units obtained from the twelve treatments and two replications, which underwent physicochemical analyses for moisture, protein, fat, ash, and fiber, as well as microbiological analyses for the best treatment (mesophilic aerobes, total coliforms, salmonella, and E. coli). According to the sensory analyses, the treatment that achieved the highest acceptability was treatment eight (a1=14°C; b1=20min; c1=24%), which was superior to the other treatments in terms of acceptance. It is a recommended treatment, being a safe and suitable product for consumption as it complies with the permissible limit according to the NTE INEN 1344-96 standard. Additionally, treatment eight had a favorable yield calculation value of 89.95%.